Alcohol Use, Alcohol-Related Outcome Expectancies, and Partner Aggression among Males Court-Mandated to Batterer Intervention Programs: A Brief Report - Brasfield, Hope (J Interpers Violence, 2014)
Additional work is needed to determine how and/or why the relationship between alcohol use and increased risk for partner aggression exists. Researchers have begun to examine whether alcohol-related outcome expectancies (i.e., beliefs about the cognitive and behavioral effects of alcohol) are associated with partner aggression irrespective of alcohol use. We examined the relationship between alcohol use, alcohol expectancies, and partner aggression among 360 males arrested for a domestic violence offense and court-mandated to treatment. Results indicate that certain alcohol expectancies do play a role in the relationship between alcohol use and some forms of partner aggression.